Preparation and Characterization of Di-, Tri-, and Tetranuclear Schiff Base Complexes Derived from Diamines and 3,4-Dihydroxybenzaldehyde - Ahlam Jameel Abdulghani; Asmaa Mohammed Noori Khaleel (Bioinorganic Chemistry and Applications)
A series of new di-, tri-, and tetranuclear Co(II) and Cu(II) complexes of three new diSchiff base ligands were synthesized by two different methods. The first method involved the synthesis of the three ligands from condensation reaction of 3,4-dihydroxybenzaldehyde (L′H2) with ethylenediamine (en), o-phenylenediamine (o-PD), or 4,5-dimethyl-1,2-phenylendiamine (DMPD) in a mole ratio of 2 : 1 followed by the reaction of the resulting Schiff bases ligands with Cu(II) or Co(II) ions in the presence of 2,2′-bipyridyl (L) to form the di- and trinuclear metal complexes. The second method involved the condensation of the copper complex LCu(II)L′ (L = 2,2′-bipyridyl, L′ = 4-formylbenzene-1,2-bis(olate)) with en, o-PD, or DMPD in a mole ratio of 2 : 1, respectively, followed by reaction with CuCl2 or Cu(ClO4)2 to form di-, tri-, and tetranuclear copper (II) complexes, respectively. The structures of the ligands and metal complexes were characterized by elemental analyses, NMR, and FTIR spectra. The geometries of metal complexes were suggested according to elemental analysis, electronic spectra, thermal analyses, atomic absorption, and magnetic moments and conductivity measurements.